2019
DOI: 10.1051/0004-6361/201935591
|View full text |Cite
|
Sign up to set email alerts
|

Average surface flows before the formation of solar active regions and their relationship to the supergranulation pattern

Abstract: Context. The emergence of solar active regions is an important but poorly understood aspect of the solar dynamo. Aims. Knowledge of the flows associated with the rise of active-region-forming magnetic concentrations through the near-surface layers will help determine the mechanisms of active region formation. Methods. We used helioseismic holography and granulation tracking to measure the horizontal flows at the surface that precede the emergence of active regions. We then averaged these flows over about sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 34 publications
9
33
0
Order By: Relevance
“…3.5. This converging flow is consistent with that reported by Birch et al (2019). For the two higher-flux subsamples, the converging flow is spatially more extended than for the lower-flux ones.…”
Section: Flows As a Function Of Time And Magnetic Fluxsupporting
confidence: 91%
See 1 more Smart Citation
“…3.5. This converging flow is consistent with that reported by Birch et al (2019). For the two higher-flux subsamples, the converging flow is spatially more extended than for the lower-flux ones.…”
Section: Flows As a Function Of Time And Magnetic Fluxsupporting
confidence: 91%
“…Their work confirms inflows of about 20-30 m s −1 that extend about 10 • from the AR. Birch et al (2019) found a compact (less than 2 • ) converging flow of about 40 m s −1 in the day before active region emergence, using both LCT and helioseismic holography as independent methods for flow inferences on the surface. Comparisons of flows derived with LCT and local helioseismology showed that the two methods agree well (Švanda et al 2013;Birch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“… Birch et al (2016) found by averaging over the emerging active regions in the SDO/HEAR survey that there are no significant outflows during emergence, although these surface outflows are predicted by thin flux tube theory. Birch et al (2019) did, however, find an average east-west elongated prograde flow just prior to emergence. We now turn our attention to the evolution of the tilt angle and Joy’s law.…”
Section: Introductionmentioning
confidence: 72%
“…It is known that there is a relationship between the supergranulation pattern and where flux emergence occurs ( Birch et al 2019 ). We speculate that if the supergranulation is guiding the initial emergence process an alternative explanation for our results is that the emergence into predominantly east-west aligned north-south converging flows ( Birch et al 2019 ) leads to a preference for east-west alignment of the polarities. Why the emergence location is preferentially in east-west aligned inflows is not clear.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation